Live Streaming, Online Customer Review, Cashback Promotion on Product Purchase Interest on Shopee Features (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: Analyzing the Influence of Live Streaming, Online Customer Review, Cashback Promotion on Product Purchase Interest on Shopee FeaturesDesign/Methode/Approach: Quantitative method with linear regression design is used to test the impact of each feature on product purchase interest. Data collection is done through a survey distributed to consumers who actively shop at ShopeeResearch Finding : Research This show that live streaming has influence positive and significant to interest buy products , with beta value 0.318 and significance 0.002 (p